Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.4049/jimmunol.1000631
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two IgD+ B Cell Populations in Channel Catfish,Ictalurus punctatus

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(119 citation statements)
references
References 72 publications
7
109
0
2
Order By: Relevance
“…For example, discoveries of IgM -IgD C subsets in catfish led to identification of similar subsets in human respiratory mucosa. 113,148 Similarly, the discovery of phagocytic B cells in fish, including catfish, has recently led to a re-examination of the characteristics and evolution of mammalian B-1 and B-2 cells. 7 On a molecular scale, functional studies of gene components critical to mucosal immune responses in catfish, will likely highlight unexplored, yet conserved, roles of orthologous genes in higher vertebrates (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, discoveries of IgM -IgD C subsets in catfish led to identification of similar subsets in human respiratory mucosa. 113,148 Similarly, the discovery of phagocytic B cells in fish, including catfish, has recently led to a re-examination of the characteristics and evolution of mammalian B-1 and B-2 cells. 7 On a molecular scale, functional studies of gene components critical to mucosal immune responses in catfish, will likely highlight unexplored, yet conserved, roles of orthologous genes in higher vertebrates (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There are 3 types of IgDC cells: IgMC/IgDC B cells, IgM-/ IgDC B cells, and an IgDC granulocyte population that express exogenously-derived IgD by means of a putative IgD-binding receptor and are negative for IgD, IgM, and TCR transcript. 113,114 Intriguingly, analysis of secreted IgD transcripts shows the absence of a V domain, and IgM-/IgDC B cells are thought to expand in response to certain pathogens and the Fc region serves as a pattern recognition molecule, similar to human IgD. Currently no work has been carried out examining the role of this B cell subset in the mucosal sites of the channel catfish.…”
Section: Adaptive Immunity At Catfish Mucosal Barriersmentioning
confidence: 99%
“…In human respiratory mucosa, the IgM À /IgD þ B cells expressed almost only Igl chain (Chen et al, 2008;Liu et al, 1996). In teleost, catfish IgM À /IgD þ B cells showed preferential usage of Igs (Edholm et al, 2010 (Xu et al, 2013;Zhang et al, 2010Zhang et al, , 2011, the mucosal IgT (especially in mucus) might also preferentially use IgLs, which needs to be further explored. On the other hand, the preferential expression of these IgL isotypes must be regulated in some certain patterns, as the two models proposed for the regulation of mammalian k or l rearrangement: the regulated/ ordered model and the stochastic model (Edholm et al, 2011;Mostoslavsky et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In teleost, rainbow trout peripheral blood leukocytes (PBLs) expressed IgLkG to IgLs at a ratio of approximately 85:15 (Timmusk et al, 2000), while catfish serum IgM associated IgLkF and IgLkG were at a ratio of 60:40 (Lobb, 1986). Recently, catfish IgM À /IgD þ cells were found only express Igs (Edholm et al, 2009(Edholm et al, , 2010. However, the investigation that human without l or k exhibited no striking immune deficiency (Gorman and Alt, 1998) together with the discovery that the certain classes of antibodies without L chain in camel (Nguyen et al, 2000), bovine (Hamerscasterman et al, 1993) and shark (Greenberg et al, 1995) had a normal function indicated that IgL might be less important in binding antigen.…”
Section: Introductionmentioning
confidence: 99%
“…This was followed by the discovery of a similar multi-domain IgD in Xenopus (Zhao et al, 2006) and in other teleosts (Hordvik et al, 1999;Srisapoome et al, 2004;Stenvik & Jorgensen, 2000). IgD has subsequently been found in the genome of many other lower vertebrates and in protherian mammals (reviewed by Edholm et al, 2010). Collectively these studies would morph into the realization that IgD and IgM are the primordial vertebrates Ig isotypes (Ohta & Flajnik, 2006;Bengten et al, 2006).…”
Section: The Case Of Mammalian Igdmentioning
confidence: 99%